Defending Trinity College Dublin, Easter 1916 : Anzacs and the rising - Sweetman, Rory (Four Courts Press, 2019)
Little has been written on Trinity College's role in Easter Week 1916 as a "loyal nucleus" dividing the insurgents and providing a counterweight to rebel headquarters in the GPO. The college is usually mentioned in the context of the rebels' alleged failure to attempt its capture, and its co-option as a barracks in the later stages of the rebellion. This book reveals how five New Zealanders, acting as the core of a squad of colonial troops, provided a vital shield to protect Trinity from capture. Had the college fallen to the surprise attack launched on it by the rebels on Easter Monday, it's 324th year may well have been its last. Nothing less than heavy and prolonged artillery would have sufficed to defeat the occupiers. Letters written home by the Kiwi soldiers give fresh insight into important aspects of the insurrection and help to answer questions left unasked in previous studies. How close did Trinity come to being a central battleground in the Rising? How and why did it escape this grisly fate? And, not least, what might have happened but for the timely intervention by the colonial troops? This book puts this neglected episode into an imperial context, with Dublin as a theater of battle in a global war.